Konservasi Eksosistem Pesisir Dan Pendidikan Lingkungan Melalui Pembibitan Mangrove Oleh Mahasiswa - Hami, Imelda Wilhelmina Mutiara; Boikh, Lebrina Ivantry (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2024)
This writing reviews the implementation of a student service program that focuses on mangrove nurseries, with the aim of supporting conservation through environmental education. The nursery process involves preparing the land, collecting mangrove propagules, and transferring the seedlings to the nursery. These steps aim to support ecological awareness among university students, so that they can become a generation that cares about the environment and understands Indonesia's strategic role as a maritime nation. This research also emphasizes the importance of periodic monitoring and maintenance of mangrove seedlings to ensure healthy and sustainable growth. The results of this study provide a practical view of the contribution of higher education in the formation of maritime character and ecological awareness through mangrove nurseries. The implication is to strengthen maritime character and increase ecological awareness among students and Indonesian society more broadly.